Intraspecific, interspecific, and seasonal differences in the diet of three mid-sized carnivores in a large neotropical wetland - Bianchi, Rita de Cassia [UNESP]; Campos, Renata Calixto; Xavier-Filho, Nilson Lino; Olifiers, Natalie; Gompper, Matthew E.; Mourao, Guilherme (Springer, 2014)
The diet and partitioning of food resources among mid-sized mammalian carnivores is poorly known, especially in the tropics. We evaluated the resource partitioning between Leopardus pardalis (ocelot), Cerdocyon thous (crab-eating fox), and Nasua nasua (brown-nosed coati) in the Pantanal of Brazil. Between December 2005 and February 2008, we collected data necessary to better understand interspecific, intraspecific, and seasonal variability in diet. Food habits were assessed by analysis of feces (n = 293) collected from known individuals (n = 128), and differences in dietary composition were evaluated through nonmetric dimensional scaling using the Jaccard similarity index. The main diet differences were observed between the specialist ocelot and the more generalist crab-eating fox and brown-nosed coati. Crab-eating foxes and brown-nosed coatis preyed on arthropods, fruits, and vertebrates whereas ocelots preyed almost entirely on vertebrates, mainly rodents and snakes. Ocelots' consumption of snakes was the highest ever recorded, as was the extent of carnivory by brown-nosed coatis. For the crab-eating fox and the brown-nosed coati, there were large differences between the use of fruits and animal foods in the wet and dry season. Yet for both species there were no significant differences in the diets of males and females. Despite the conspicuous sexual dimorphism and spatial segregation that are typical of brown-nosed coatis, the results do not support the hypothesis that size dimorphism is primarily an adaptation to reduce intersexual competition for food. Rather, dimorphisms and patterns of space use may be more related to competition among males for access to females.
Keywords: Cerdocyon thous; Frugivory; Intersexual competition; Leopardus pardalis; Nasua nasua